Intact Glycocalyx of Intestinal Mucosa in Intraabdominal Infection: an Investigation Using Blood Group Antigen - Toar Jean Maurice Lalisang; Mohamad Sadikin; Ridho Ardhi Syaiful; Novi Silvia Hardiany; Yefta Moenadjat (Acta Medica Indonesiana)
Background: intestinal glycocalyx plays a role in bacterial translocation as the pathogenesis sepsis derived from intra-abdominal infections that vulnerable in certain blood types. However, the link between intestinal glycocalyx in specific types of blood groups and abdominal infections remains unknown. This study aims to find out the condition of intestinal glycocalyx in certain blood types with intraabdominal sepsis. Methods: descriptive study involved subjects with intraabdominal infections who underwent laparotomy. Samples are in the form of intestinal specimens. The measurement of intestinal glycocalyx proceeded by the ELISA method using blood group antigens (A and B). Expression data on the secretors were analyzed using the Kolmogorov – Smirnov test followed by parametric comparisons using ANOVA and t-tests. Results: there were 32 subjects with intra-abdominal infections studied in this study. All of them are secretors and express A and B antigens strongly. We found no difference between intraabdominal infections in those with complications or without complications. Blood type O is a predominant blood type found (43.8%). Escherichia coli is the most commonly found microbe in the culture (61.3%). Conclusion: this study shows there is no disrupted intestinal glycocalyx of sepsis patients caused by intraabdominal infection.